A critique of historical frameworks in Mindanao-Sulu historiography - Asain, Calbi A. (2011)
This paper is an attempt to review the historical frameworks articulated by selected historians in the writing of the history of Mindanao and Sulu. These reputable historians in the country or abroad, who have lived or have done historical researches on Mindanao and Sulu, have come up with their own historical frameworks for the region, which could help and guide Filipino historians, both local and national, in the difficult task of writing the general history of Mindanao and Sulu. This critique is far from being exhaustive. Rather, it is simply an attempt to survey which frameworks are best suited to the writing or rewriting of the general history of Mindanao and Sulu. It also looks into the possibility of putting together the best elements of the frameworks under scrutiny to possibly design a common framework for Mindanao and Sulu ? something that can hold the readers? attention by virtue of its ability to depict the drama and interest inherent in the exciting past of the region. It must be admitted, nevertheless, that it is indeed tormenting to determine and develop a single historical framework for Mindanao and Sulu. The history of the region is a complex one because of the diversity of its inhabitants, who seemingly belong to three separate ?nations,? namely: the indigenous people or the highlanders, the Muslims, and the Christian migrants. Such a reality, however, should not deter us from pursuing a fitting historical framework for Mindanao and Sulu, which also ought to reflect the character and nature of our national historiography. Given the right time and the right framework, the historiography of Mindanao and Sulu may prove manageable, instead of being formidable, for local and national historians alike to undertake.